Influence of Using Different Preparation Methods on the Properties of ZnO Nanoparticles - Athraa Hadi; Nada Abbas (Iraqi Journal of Physics)
Zinc oxide nanoparticles (ZnO NPs) were created using two different preparation methods: chemical precipitation and the green method using the leaves of Ficus carica extract. The nanoparticles were examined using X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), and Energy Dispersive X-ray Spectroscopy (EDX). Analytical techniques such as XRD were applied to verify the crystallinity of ZnO NPs as well as used to calculate the crystal size for the prepared samples. The XRD pattern exhibited a hexagonal structure, and the mean diameter of the crystal size for ZnO NPs prepared by chemical precipitation was 27.44 and 33nm for ZnO NPs prepared by the biological method. Nanoparticles of ZnO have a spherical shape, as examined by FE-SEM. The EDX test indicated the existence of peaks corresponding to zinc and oxygen. The surface properties, such as root mean square roughness (Rq) and average roughness (Ra) were examined by atomic force microscopy (AFM), where Rq and Ra were 35.8 and 29.3 nm, respectively. The ZnO NPs made using chemical precipitation and biological methods were studied with UV-visible spectroscopy (UV-Vis) to look at the absorption spectra, and it was found that the absorption spectrum increased with the green method.